Development of Herbaceous Plant's Pocket Book as Biology Learning Media to Improve Learning Outcomes in Plant Anatomy and Morphology Courses - Arbaul Fauziah; Mivida Novi Soviona (Universitas Negeri Padang Address: Biology Education Study Program Faculty Mathematics and Natural Science (FMIPA) Jl. Prof. Dr. Hamka Air Tawar Barat, Padang-West Sumatera-Indonesia Telp. +62751-7057420 - Fax.+62751-7058772 - Ph. +6281363229286, 2022)
Trinil Sky Root is a tour that has various types of plants, one of which is herbaceous plants. Based on the surey results, it was shown that all students did not have specific information that discussed the morphology of herbaceous plants so that students had difficulties in learning it. Whereas one of the factors supporting the success of the learning process is the use of learning media. Learning media is very important in supporting learning activities so that it is expected to realize a good teaching and learning process and have a positive impact on learning outcomes. The purpose of this study was to develop a biology learning media in the form of a pocket book of herbaceous plants and to find out its validity. This type of research is R&D with the ADDIE development model. The trial subjects of this research were biology students at UIN Sayyid Ali Rahmatullah Tulungagung. The results of the analysis of the need for learning media for plant morphology pocket books, it can be seen that almost all Biology Tadris students already knew about herbaceous plants. However, some respondents have not been able to correctly name the characteristics of herbaceous plants, so there was need for learning resources that can facilitate achieving learning outcomes. The results of material expert validation were obtained at 96.4% (very valid) and media experts obtained a percentage of 88% (very valid). At the respondent's trial stage, the average post-test score was greater than the pre-test score, respectively 88.4 and 68.4. Then, the average readability test results of respondents got an average percentage of 93.9% (very valid). Thus, the herbal plant pocket book learning media at Trinil Sky Root Tourism is very suitable to be used as an alternative to support learning activities.